Incidence of Fractures after Cardiac and Lung Transplantation: A Single Center Experience - Aileen Hariman; Charles Alex; Alain Heroux; Pauline Camacho (Journal of Osteoporosis)
Osteoporotic fractures are well-known complications of organ transplantation. Fracture rates up to 35% have been previously reported following heart and lung transplantations. Our institutional pretransplant protocols include DXA scans, vitamin D screening, and appropriate antiresorptive therapy. We aimed to assess the incidence of fragility fractures following cardiac or lung transplantation. In a retrospective study 210 electronic medical records of patients who underwent LT (110 men, 100 women) and 105 HT (88 men, 17 women) between 2005 and 2010 were analyzed. Both clinical and radiographic fractures were recorded. DXA scans were obtained immediately after transplant. 17 out of 210 LT patients (8.0%) had fractures after transplantation and 9 out of 105 HT patients (8.6%) had fractures. The median time to the first fracture was 12 months and the mean time was 18 months for both LT and HT. In the HT recipients, the median femoral neck T score was statistically lower in the fracture group versus the nonfracture group. Similar results were seen in the LT patients. Conclusion. Our findings demonstrate a much lower incidence of fractures in heart and lung transplant recipients in comparison with earlier reports. Comprehensive bone care and early initiation of antiresorptive therapy are possible contributors to these improved outcomes.